An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

L'investissement : étude juridique - Grundeler, Guillaume (Aix-Marseille Université, 2014)
L'investissement est une notion récente dans la sphère juridique. Voici quelques années, elle n'était encore employée que dans la règlementation relative au contrôle des investissements étrangers. C'est que, si le droit n'ignorait pas l'investissement, il le saisissait presque uniquement à travers d'autres notions, tels l'apport en société ou le mouvement de capital. Depuis lors, le mot a été très largement juridicisé. Pour s'en tenir à deux exemples, on peut ainsi relever que, dans notre ordre interne, l'existence d'un investissement permet une durée contractuelle longue et que, dans l'ordre international, la qualification d'investissement est aujourd'hui une condition de la compétence des tribunaux arbitraux statuant sous l'égide du Cirdi.Cet accès spontané de l'investissement à la juridicité s'est malheureusement accompagné de certaines incohérences. Ainsi, le mot est parfois employé de manière excessivement large, comme en droit des marchés financiers, où il désigne toute opération relative à un instrument financier. De même, en droit des régimes matrimoniaux, ce que la Cour de cassation nomme les « dépenses d'investissement » recouvre en réalité l'ensemble des dépenses immobilières. Parfois, à l'inverse, certaines opérations dont la qualification d'investissement ne fait aucun doute continuent d'être envisagées à travers des notions qui en sont le simple reflet. L'objet de la thèse est donc de rétablir une certaine cohérence dans l'emploi du mot investissement en proposant une définition juridique de la notion et en esquissant certains éléments du régime qui s'y attache.
Keywords: Apport; Arbitrage d'investissement; CIRDI; Capital contribution; Centre international pour le réglement des différends relatifs aux investissements; Civil liability; Contrôle des investissements étrangers; Droits sui generis du producteur de bases de données; Duration of the contract; Durée contractuelle; Foreign investment regulation; Foreign investments; France; Free-Riding; ICSID; Investissements; Investissements étrangers; Investisseur; Investment arbitration; Investments; Investor; Parasitisme; Responsabilité civile; Return on capital; Rémunération; Sui generis right of the producer of a database

Les produits structurés et la protection de l'investisseur - Gomez Richa, Lucia (Université de Genève, 2014)
La présente étude propose une analyse juridique des produits structurés (art. 5 LPCC), qui la conduit à une réflexion plus large quant à la protection de l'investisseur en droit suisse, de lege lata mais également au regard de l'avant-projet de loi sur les services financiers. L'étude met tout d'abord en lumière les incohérences et les insuffisances du système juridique actuel. Elle propose une définition nouvelle des produits structurés assurant une cohérence au système. Avec comme fil conducteur et illustration la complexité des produits structurés, la thèse explique et critique le retard de la réglementation suisse en matière de protection des investisseurs, tant s'agissant de la conception juridique de l'investisseur que de la concrétisation des règles de conduite par l'émetteur et les distributeurs. Elle expose et discute les règles et pratiques existantes visant à répondre à certains des enjeux posés. Enfin, la thèse énonce des propositions d'amélioration à ces règles, en grande partie relayées par l'avant-projet de loi sur les services financiers.
Keywords: Anlage (Investition); Anlagefonds; Derivative Finanzinstrumente; Instruments dérivés (finances); Investisseurs directs; Produits structurés; Produits structurés (finances); Protection; Protection de l'investisseur; Risque financier; Réglementation des marchés financiers; Schweiz; Sociétés d'investissement; Suisse

Venture capital: valor da informação, riscos e instrumentos para sua mitigação - Silva, Fernando César Nimer Moreira da (Universidade de São Paulo, 2014)
Venture capital é espécie de empreendimento que vincula dois agentes econômicos, empreendedor e investidor, visando ao desenvolvimento de uma ideia inovadora para posterior comercialização no mercado. O empreendedor é detentor de conhecimento sobre a ideia e o investidor possui os recursos para desenvolver o projeto. O negócio se diferencia dos demais pelo alto grau de incerteza e risco do empreendimento e requer o uso de tipos contratuais adequados para sua limitação. O projeto se inicia com a etapa de contratação, na qual as partes negociam a divisão de riscos e retorno do negócio, seguindo-se a etapa de monitoramento do desenvolvimento das atividades. Ao final ocorre o desinvestimento, com a saída do investidor e venda do negócio. Do ponto de vista da Economia, utilizamos a Teoria dos Jogos e apresentamos os problemas informacionais, riscos e incertezas do negócio, e os incentivos para organizar a cooperação entre as partes. Do ponto de vista de Finanças, debatemos a decisão de financiamento do negócio e as alternativas para diversificação dos riscos do investimento, isto é, a possibilidade de limitação dos riscos pela adoção de estratégias de contenção, que aumentam o interesse em contratar o negócio. Do ponto de vista do Direito, avaliamos qual a estrutura contratual ideal para organizar esse tipo de empreendimento. Analisamos as principais formas usadas para organização do negócio, em especial as sociedades limitadas e as sociedades anônimas fechadas. Avaliamos o suporte normativo aplicável, com destaque para a possibilidade de limitação dos riscos do projeto pela aplicação das normas de Direito Societário a esses empreendimentos. Os principais riscos aplicáveis são os riscos de contratação do negócio, os riscos de alocação do poder de decisão entre os sócios e os riscos de interrupção prematura do projeto. Devido à natureza e características do negócio de venture capital, concluímos que esse tipo de projeto é mais bem organizado como um contrato plurilateral e que não há tipo contratual ideal para alinhar os interesses. Dos tipos existentes, a sociedade anônima fechada é o mais adequado, mas incapaz de limitar todos os riscos do negócio. A conclusão é confirmada, parcialmente, pelas evidências empíricas apresentadas. Venture capital is a business that links two economic agents, entrepreneur and investor, aiming to develop an innovative idea for future sale on the market. The entrepreneur holds knowledge about the idea and the investor has the resources to develop the project. It is distinguished from others by the high degree of uncertainty and risk of the project and requires the use of appropriate contract types for its restriction. The project begins with the contracting stage, in which the parties negotiate the division of risks and return business, followed by the monitoring of the development of the business activities. At the end occurs the divestment, in which the finished business is sold by the investor. From the point of view of Economics, we use Game Theory to present the informational problems, business risks and uncertainties, and the incentives to organize the cooperation between the parties. From the standpoint of Finance, we discuss the decision to finance the business, and alternatives for risk diversification, that is, the possibility of limiting the risks by adopting containment strategies that may increase the interest in contracting. From the point of view of Law, we evaluate the ideal contractual structure for organizing this kind of project. We analyze the main existing contract types, in particular, the limited liability companies and the closed corporations. We present our concerns about the normative support applicable to that type of business, emphasizing the Corporate Law problems. We evaluate the normative support applicable, emphasizing the possibility of limiting the project risks by applying the Corporate Law rules to such ventures. The main risks are the risks applicable to the contracting phase, the risk of incorrect allocation of decision rights between the partners and the risk of premature termination of the project. Due to the nature and characteristics of the venture capital business, we conclude that this type of design is best organized as a plurilateral agreement and that there is no contract type that can be considered ideal to align the interests. Considering all the existing types, the private corporation contract is the most appropriate form, but also unable to limit all the business risks. The conclusion is partially supported by the empirical evidence presented.
Keywords: Capital de risco; Capital-risque; Closed company; Closed corporation; Contract; Corporate finance; Direito comercial; Game theory; Instruments; Investimentos; Investment fund; Law and economics; Limited liability company; Mercado de capitais; Risk; Risque; Uncertainty; Venture capital

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments